Human-Sheldgeese conflict in agricultural landscapes: Effects of environmental and anthropogenic predictors on Sheldgeese distribution in the southern Pampa, Argentina - Pedrana, Julieta (2014)
Sheldgeese species are currently the subject of serious conservation concern and have been a source of historical conflict with agricultural interests. Here we assess the relative effects of environmental and anthropogenic predictors on Sheldgeese (Ruddy-headed Goose Chloephaga rubidiceps, Ashy-headed Goose Chloephaga poliocephala and Upland Goose Chloephaga picta) distribution in the southern Pampas at different spatial scales. These birds were declared an “agriculture plage” by the government and this conflict with humans has been so far resolved with species persecution. We evaluate whether its current wintering distribution is shaped by anthropogenic disturbances or whether it can be better explained by differences in topography and preference for wetlands, or by landscape composition and configuration. We characterized the study region using 17 potential predictors related to environmental, human and landscape characteristics. We built habitat-suitability models to examine the relative effect of the variables on the regional occurrence of Sheldgeese. We performed vehicle surveys in southern Buenos Aires province, in two years (2011–2012), surveying 9200 km of roads and recording 281 Sheldgeese flocks. Generalized additive models were used to model the presence/absence of Geese in 250-m cells. The habitat suitability models of Sheldgeese suggest that: (1) areas of low elevation surrounded by waterbodies are one of the main positive drivers of species distribution, (2) centers of human activity, which are regions with greater road accessibility, have a negative impact on species distribution, (3) heterogeneous landscape composed of croplands and grazing fields are preferred environments